How to deliver person-centred care for people living with heart failure: a multi stakeholder interview study with patients, caregivers and healthcare professionals in Thailand - Alessandra Giusti; Panate Pukrittayakamee; Kamonporn Wannarit; Lakkana Thongchot; Satit Janwanishstaporn; Kennedy Nkhoma; Sridhar Venkatapuram; Richard Harding (BMC Health Services Research, 2024)
Abstract Context Heart failure has high, growing global prevalence, morbidity and mortality, and is a leading cause of death with serious health-related suffering in low- and middle-income countries. Person-centred care (PCC) is a critical component of high-quality healthcare and is particularly vital in the context of a serious illness such as heart failure. However, there are limited data exploring PCC in this population in low- and middle-income settings. Aim The aim of this study was to explore how clinical services could respond to the PCC needs of individuals living with heart failure in Thailand, with potential for adaptation in other settings. The specific objectives were (i) to understand the experiences and needs of persons living with heart failure, their caregivers and HCPs; (ii) to explore specific practical actions that can help deliver PCC for heart failure patients in this setting. Methods Cross-sectional qualitative study. In depth, semi-structured interviews were conducted in Thailand with heart failure patients (n = 14), their caregivers (n = 10) and healthcare professionals (n = 12). Framework analysis was conducted with deductive coding to populate an a priori coding frame based on Santana et al’s PCC model (2018) and Giusti et al’s systematic review (2020), with further inductive coding of novel findings to expand the frame. The study is reported in accordance with the consolidated criteria for reporting qualitative research guidelines (COREQ). Results The findings reveal specific practice actions that deliver PCC for persons living with heart failure in Thailand, such as (i) compassionate communication by healthcare professionals; (ii) effective teamwork amongst multidisciplinary healthcare professionals; (iii) proactive responses to physical, psychosocial, relational and information needs of patients and caregivers; (iv) engaging patients and families in symptom management; (v) providing opportunities for patients to be cared for in the community; and (vi) responding to the social determinants of health, illness and healthcare access. Conclusion Person-centred healthcare systems must aim to address the social determinants of illness and place focus on community- and home-based care. Heart failure patients and caregivers must be supported to self-manage, including how to recognise symptoms and take appropriate action. Delivering PCC in such a way has the potential to improve outcomes for patients, enhance patients’ sense of agency and experiences of care, improve health equity, and reduce hospital admissions, relieving pressure on the hospital system and reducing overall costs of care.